A Study on the Development of a Model for Providing Traditional Korean Medicine and Welfare Services for Community Care - Eun-Jin Lee; Hee-Jung Lee; Danny Oh; Jung-Youn Park; Dongsu Kim; Sang-Nam Lee; Gihyun Lee; Ji-Yeon Lee; Kyeong Han Kim; Soo-Hyun Sung (Korean Pharmacopuncture Institute, 2022)
Objectives: This study aims to develop a community care model in traditional Korean medicine (TKM) by developing a community care participation model for the health of the elderly and deriving tasks to implement it. Methods: This study implemented a group interview with experts. A fact-finding survey was conducted targeting 16 local governments that are implementing a leading project to identify the status of TKM service provision and welfare service linkage in all regions. An expert group interview (FGI) targeted public and private sector experts for each job role, the former represented by those in charge of the central government's health care policy and administrative delivery system, and the latter by professors majoring in social welfare, professors majoring in health, and local TKM societies. After forming the expert groups, three expert group interviews were conducted. Results: Through collective interviews with experts, a model for providing TKM and welfare services in community integrated care was derived by dividing it into local and central government levels. The strategies and tasks for promoting TKM-oriented health welfare services were derived from 3 strategies, 8 tasks, and 20 detailed tasks. Conclusion: The core direction of the TKM health care model is the region-centered provision of TKM and welfare services. To this end, policy support for the use and linkage of health care service resources is required at the central government level, and linkage and provision of health welfare services centered on TKM are necessary through linkage and convergence between service subjects and between government health care projects.